Physical chemistry - Ball, David W. ([S.l.] : Brooks Cole, 2002)
Intended for the year long, calculus-based physical chemistry course for science and engineering majors, PHYSICAL CHEMISTRY follows a traditional organization while concentrating on core topics. The text does not cover some higher level topics-for example, photochemistry, molecular beams, thermal physics, and polymers- found in some textbooks, and rarely covered in the undergraduate physical chemistry course, but more fully explains the essential elements of the discipline. Written by a dedicated chemical educator and researcher, this text is intended for those students who are trying to learn physical chemistry-a book that works as a textbook and not as an encyclopedia. Where appropriate, there is some focus on mathematical manipulations, providing students with a review of calculus applications as applied to physical chemistry.